2020
DOI: 10.1111/jce.14346
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and clinical characteristics of atrial fibrillation in patients with inherited heart diseases

Abstract: Background: The prevalence and clinical course of atrial fibrillation (AF) in hypertrophic cardiomyopathy (HCM) is well described, though less so for other inherited cardiomyopathies (familial dilated cardiomyopathy, arrhythmogenic right ventricular cardiomyopathy, left ventricular noncompaction); and inherited arrhythmia syndromes (long QT syndrome, Brugada syndrome or catecholaminergic polymorphic ventricular tachycardia [CPVT]). We examined the frequency, clinical characteristics and AF-related management a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…This finding is consistent with prior results that found that 28.8% of patients with an inherited cardiomyopathy syndrome had AF compared with 8.2% of patients with an inherited arrhythmia syndrome. We found that disease-associated variants were most frequent in genes associated with DCM followed by AC/ARVC and HCM. There is considerable overlap among the genetic causes of DCM, AC/ARVC, and HCM, and collectively these patients may represent a genetic subtype of AF characterized by the early development of an atrial myopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with prior results that found that 28.8% of patients with an inherited cardiomyopathy syndrome had AF compared with 8.2% of patients with an inherited arrhythmia syndrome. We found that disease-associated variants were most frequent in genes associated with DCM followed by AC/ARVC and HCM. There is considerable overlap among the genetic causes of DCM, AC/ARVC, and HCM, and collectively these patients may represent a genetic subtype of AF characterized by the early development of an atrial myopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The next most common was MYH7 (13%), encoding β-myosin heavy chain, which supports prior observations that patients with HCM attributable to MYH7 variants have a significantly higher risk of AF than those with variants in other sarcomeric genes. Further supporting the potential importance of myosin heavy chain subunits on atrial structure and function, variants in MYH6 , which encodes the α-subunit predominantly expressed in atrium, were also common (7%). Other top genes were LMNA (6%), which encodes lamin A and C and is responsible for an especially arrhythmogenic form of DCM with early-onset conduction disease, ventricular tachycardia, and AF, and KCNQ1 (6%), which causes type 1 LQTS.…”
Section: Discussionmentioning
confidence: 99%
“…A higher degree of mitral valve regurgitation is found in patients with a mutation in the MYH7 gene [ 28 ], and MYH7 is proposed as one of the genes that are most commonly mutated in early-onset AF [ 29 ]; HCM patients with likely pathogenic or pathogenic mutations in MYH7 had a higher rate of incident AF compared with other sarcomeric genes [ 30 ]. AF was found to be independently associated with MYH7 variants amongst sarcomere-positive HCM [ 31 ], and a higher frequency of AF was found in patients with mutation in the MYH7 gene [ 27 , 32 ]. Missense mutations in MYBPC3 gene are proposed to be responsible for AV block [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous reports, the penetrance estimates for each discrete phenotype was low (2-9%), limiting the clinical utility of each individual result for carriers. While each phenotypic association may represent a discrete disease, we wanted to test if instead, the multiple associations reflect varying and compounding outcomes that result from underlying structural, functional, and metabolic changes stemming from TTNtvs (3,13,15,(28)(29)(30).…”
Section: Ttntv Associations With Cardio Phenotypes Are Driven By Atri...mentioning
confidence: 99%
“…By including other common symptoms such as arrhythmias and "Stage B" heart failure, it may be possible to detect the manifestations of this heart disease earlier and in a younger cohort. Indeed, TTNtv in hiPSI transcripts have also been associated with early onset atrial fibrillation (Afib), which may overlap with the well-established DCM association (13)(14)(15). Determining how the phenotypic footprint of TTNtvs extends beyond DCM may improve population-based retrospective penetrance estimates.…”
Section: Introductionmentioning
confidence: 99%